PENGAMANAN SERVER DENGAN METODE PORT KNOCKING DAN KEY AUTHENTICATION PADA LAYANAN SECURE SHELL (SSH) - Tubagus Muhammad Fawwaz Rasyid, (2021)
Implementation of more security on the server to secure data from irresponsible people by using port knocking and key authentication methods in the secure shell (ssh) service. The port knocking method is an authentication method by entering a predetermined pattern. Key authentication method is an authentication method using a public key and a private key. The results of testing server security without port knocking and key authentication methods with server security using port knocking and key authentication methods are different and server security using port knocking and key authentication methods cannot be hacked by sniffing and brute force methods. Server security is better using port knocking and key authentication methods than not using more security